The Influence of Knowledge Management on Individual Performance in Traditional Batik Craftsmen: The Mediating Role of Organizational Culture - Kusuma, Emeralda; Efendi, David; Suwarno, Suwarno; Djanegara, Moermahadi (Research Horizon, 2023)
In the modern business landscape driven by technology and information, this study explores the connections between Knowledge Management, Competitive Advantage, Organizational Culture, and Individual Performance among traditional batik craftsmen in Sidoarjo regency. The research, based on primary data collected from 73 questionnaires, rigorously tests hypotheses using regression analysis. Findings reveal that Knowledge Management positively influences Individual Performance, emphasizing the importance of effective knowledge utilization. Surprisingly, Competitive Advantage does not significantly impact Individual Performance in this context. Additionally, Organizational Culture negatively moderates the influence of Knowledge Management on Individual Performance, underlining the importance of aligning culture with knowledge practices. Notably, Organizational Culture does not effectively moderate the influence of Competitive Advantage on Individual Performance, highlighting the complex interplay between cultural factors and strategic advantages in the traditional batik industry. While limitations exist, such as extensive questionnaire items and comprehension issues, these insights offer valuable guidance for organizations seeking to optimize knowledge management practices, gain a competitive edge, and thrive in today’s dynamic global marketplace.